2005
DOI: 10.1073/pnas.0509849103
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies to myelin basic protein catalyze site-specific degradation of their antigen

Abstract: Autoantibody-mediated tissue destruction is among the main features of organ-specific autoimmunity. This report describes ''an antibody enzyme'' (abzyme) contribution to the site-specific degradation of a neural antigen. We detected proteolytic activity toward myelin basic protein (MBP) in the fraction of antibodies purified from the sera of humans with multiple sclerosis (MS) and mice with induced experimental allergic encephalomyelitis. Chromatography and zymography data demonstrated that the proteolytic act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
239
1
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 174 publications
(249 citation statements)
references
References 39 publications
6
239
1
3
Order By: Relevance
“…It was recently shown that incubation of many individual IgGs with iodoacetamide (a specific inhibitor of thiol proteases) or pepstatin A (a specific inhibitor of acidic proteases) has moderate effect (5-15%) on SLE Ab-dependent hydrolysis of MBP [9]; the same was demonstrated for MS IgGs, IgAs and IgMs [27][28][29][30][31]. However, PMSF, AEBSF (specific inhibitors of serine proteases), and EDTA (an inhibitor of metalloproteases) significantly suppressed the proteolytic activity of SLE and MS pIgGs in the case of MBP and OPs as substrates [9].…”
Section: Discussionmentioning
confidence: 89%
See 4 more Smart Citations
“…It was recently shown that incubation of many individual IgGs with iodoacetamide (a specific inhibitor of thiol proteases) or pepstatin A (a specific inhibitor of acidic proteases) has moderate effect (5-15%) on SLE Ab-dependent hydrolysis of MBP [9]; the same was demonstrated for MS IgGs, IgAs and IgMs [27][28][29][30][31]. However, PMSF, AEBSF (specific inhibitors of serine proteases), and EDTA (an inhibitor of metalloproteases) significantly suppressed the proteolytic activity of SLE and MS pIgGs in the case of MBP and OPs as substrates [9].…”
Section: Discussionmentioning
confidence: 89%
“…It was recently shown that, anti-MBP IgGs from the sera of patients with MS [27][28][29][30][31] and SLE [9] efficiently hydrolyze globular MBP but not many other tested proteins. No activity was found for IgG fraction of healthy donors in the hydrolysis of MBP or different OPs (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations